TINJAUAN YURIDIS ALASAN PEMBENAR PENGAHAPUS PIDANA MENURUT PASAL PASAL 50 DAN 51 KITAB UNDANG-UNDANG HUKUM PIDANA - Dadang Firmanto (Universitas 17 Agustus 1945 Samarinda, 2014)
AbstractState based on law (rechtsstaat), laying down the law as the rule in state law that concrete is in the form of legislation is written (positive law) or in the form of verbal maintained in public life, Talking legal means to speak about the situation, the situation and the context of that has to do with the law itself.In criminal law there are several reasons that can be used as a basis for the judge to impose law / criminal to the perpetrators or the accused are executed in court, because it has committed a crime reasons eraser criminal is that allows someone doing actual deeds have mememnuhi formulation of offense , but not convicted, for example, mental illness (article 44 of the Criminal Code) on the power force (Article 48 of the Criminal Code), the defense forced (article 49 of the Criminal Code), the implementing legislation (Article 50 of the Criminal Code) and the duties of office (article 51 of the Criminal Code )The need for regulation in the articles and a more detailed description on the bill of the Criminal Code that is the abolition of criminal derngan justification and an excuse pleased with the accountability of the perpetrators because based menjlankan laws undnag or duties of office, therefore it is suggested that the provisions of criminal offenses crime also other crimes, equipped with the formulation of elements of the offense, memudahlan It is intended for implementation of provisions on the type of offenses concerned.